Export stability of crude palm oil in Indonesia - Redha Roylita, Dede; Vivi Silvia, Aliasuddin, (Opción, 2019)
This study aims to analyze the export stability of crude palm oil in Indonesia both on short and long-term basis during the time period of 2005: Q1 - 2017: Q4 by using the Autoregressive Distributed Lag (ARDL) model. The results showed that in long-term estimation only Indonesian crude palm oil production was giving a significant positive effect on Indonesia's crude palm oil export volume. In conclusion, the Indonesian government needs to diversify crude palm oil derivative products for additional value and addressing the crude palm oil dependency on foreign markets.